Political Reforms in Qatar. - Battaloglu, Cihat (Gulf Studies Ser., 2018)
In the past decade, Qatar has emerged as one of the world's most proactive mediators in the international arena. It has also experienced a number of domestic changes to its economic infrastructure, welfare system and political system, along with material improvement in its citizens' standard of living. Nonetheless, despite such radical and rapid advances, political reform in Qatar has proved to be relatively tentative. This book examines political reforms in Qatar from an analytical, normative and ideological perspective. It applies the main concepts and theories found in the literature on dem.